Parent-led group CBT for childhood anxiety problems :clinical outcomes of a new treatment option within the public mental health services in Iceland - Þórunn Sif Guðlaugsdóttir 1988- (2023)
Background: Anxiety affects up to 6,5% of children at any given time, and without appropriate treatment, it is unlikely that they will recover. Cognitive Behavioral Therapy (CBT) is effective in treating anxiety disorders but only a small percentage of children have access to CBT. To increase access to CBT for childhood anxiety problems, therapist-guided parent-led CBT (GPD-CBT) has been designed. This study aims to examine the effectiveness of GPD-CBT in primary care for 5 - 12 years old children who have an anxiety problem. Method: The participants of the study were parents of 42 anxious children that attended one of seven group treatments at their local primary care. The effectiveness of the treatment and other aspects of it (e.g. participant satisfaction, children's anxiety symptoms) were assessed with 5 questionnaires administered weekly. Results: Overall findings were significantly positive, with moderate to large effects, indicating that the treatment decreased anxiety symptoms and participants were highly satisfied with the treatment. These findings provide further evidence of the capability of GPD-CBT in treating childhood anxiety problems. Conclusions: This study provides promising evidence for GPD-CBT in treating childhood anxiety problems in primary care in Iceland. Furthermore, parents reported high satisfaction with the treatment. However, the findings of this study were not compared to a waiting list or to another treatment intervention. Keywords: childhood anxiety, CBT, parent-led treatment, GPD-CBT